2008
DOI: 10.1021/jp805538j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Noble Metal (Pd, Pt, Au, Ag) Nanostructured Materials Confined in the Channels of Mesoporous SBA-15

Abstract: Highly dispersed metal (Pd, Pt) nanoparticles and uniformly distributed metal (Au, Ag) nanowires have been synthesized in ordered mesoporous silica SBA-15 via conventional incipient wetness impregnation followed by novel glow discharge plasma reduction. N 2 adsorption-desorption isotherms and the low-angle X-ray diffraction (XRD) patterns indicate that the parent ordered mesoporous structure was well-maintained during the synthesis process. The wide-angle XRD patterns and transmission electron microscope image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
146
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(152 citation statements)
references
References 32 publications
3
146
0
3
Order By: Relevance
“…2(A), we can observe that all diffraction peaks of Pd confined samples shift slightly to lower angles, corresponding to a tiny increase of d 1 0 0 and a 0 , as listed in Table 1. This shift suggests that the frameworks of the silica host are slightly enlarged during the synthesis process [13]. The wide-angle XRD (WA-XRD) and EDS (insert) patterns of all Pdsupported catalysts are shown in Fig.…”
Section: Samplementioning
confidence: 95%
See 1 more Smart Citation
“…2(A), we can observe that all diffraction peaks of Pd confined samples shift slightly to lower angles, corresponding to a tiny increase of d 1 0 0 and a 0 , as listed in Table 1. This shift suggests that the frameworks of the silica host are slightly enlarged during the synthesis process [13]. The wide-angle XRD (WA-XRD) and EDS (insert) patterns of all Pdsupported catalysts are shown in Fig.…”
Section: Samplementioning
confidence: 95%
“…Therefore, the exploration of new preparation methods is still very urgent. Liu and co-workers [13] synthesized the monodispersed Pd nanoparticles in the interior surface of SBA-15 channels via a glow discharge plasma reduction approach, but the average Pd particle size was still unsatisfactory (ca. 8.2 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the (1 0 0), (1 1 0) and (2 0 0) reflection becomes more intense and prominent with the decreasing of Al content, indicating that the hexagonal order is decreased to some extent with the introduction of Al species. Besides, it can be noticed that all diffraction peaks of Pd/SC-x samples shift slightly to lower angles (i.e., d 100 and a 0 are slightly enlarged [22]) compared with the Pd/SBA-15 and Pd/SBA-15-T materials, suggesting that Al atoms are introduced into the frameworks of the SC-x host as the Al-O bond length is longer than that of Si-O bond. Fig.…”
Section: Xrd and N 2 Adsorption/desorptionmentioning
confidence: 99%
“…On the other hand, recent work suggested that noble metal confined catalysts possess high catalytic activity and stability as the pore channels of supports have the potential ability to inhibit active particles growth and aggregation during reactions [22]. Various strategies were developed for incorporating metal nanoparticles into mesoporous silica, such as chemical vapor deposition [23], wet impregnation [7,16,24,25] and ion exchange [26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, nonequilibrium cold plasma preparations with high electron temperatures (as high as 10 4 K) and very low gas temperatures (as low as room temperature) can generate materials similar to the virus template. 50 With such high electron temperatures, nucleation and growth kinetics vary substantially from that of the conventional thermal method. Moreover, the development of new characterization techniques for nanomaterials is extremely important.…”
mentioning
confidence: 99%